Giving Voice to Values as a Leverage Point in Business Ethics Education - Arce M., Daniel G. (Journal of business ethics, 2015)
The Giving Voice to Values (GVV) pedagogy and curriculum is described as an example of a powerful leverage point in the integration of business ethics and values-driven leadership across the business curriculum. GVV is post-decision-making in that it identifies an ethical course of action and asks practitioners to identify (i) who are the parties involved and what’s at stake for them; (ii) what are the main arguments (reasons and rationalizations) to be countered; and (iii) what levers that can be used to influence those who are in disagreement. The internalization of GVV’s constructs allows faculty to comfortably raise and endorse ethics as part of the natural order of business decision-making because the stakes of doing so have been normalized. Methods for introducing and using GVV in undergraduate through MBA courses are given. An illustration is given for economics courses.